Trajectories and the influencing factors of behavior problems in preschool children: a longitudinal study in Guangzhou, China. Issue 1 (December 2016) - Bao, Peng; Jing, Jin; Jin, Yu; Hu, Xumin; Liu, Buyun; Hu, Min
Abstract Background Since child mental health problem was a global health issue, many researchers in western countries has focused on the trajectory of it to provide evidence for prevention programs. We designed this study to determine the trajectories of children's behavior problems, and to explore the effect of parent predictors on children's behavior problems in Guangzhou, China. Methods Children (N = 1480) for this longitudinal, population-based survey, were recruited from eight regular kindergartens (October, 2010) across four districts in Guangzhou. Repeated measurement design analysis was used to compare the variation in behavioral problems by gender, only child status, and temperament. Logistic regression was applied to analyze the effect of parents' risks (maternal depression, parenting style) on the change in child problem behaviors. Results The scores of behavior problems (externalizing, emotional, social communication problems) were stable during the entire preschool period by gender and child number. Children with difficult temperament exhibited more problem behaviors than children with easy temperament in the early years, and the misbehaviors declined significantly over time. Moreover, maternal depression and the increase in excessive interference/over protective or punishing parenting strategies resulted in an increase in child behavior problems. Conclusion There was no difference between the only-child status and child with siblings in the trajectory of problem behaviors. Parent factors were significant predictions of trajectory of child behavior problem during preschool age.